Europec 2015 2015
DOI: 10.2118/174371-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Salinity, CO2 Solubility, and Gas Composition on Coal Wettability

Abstract: Geological sequestration of CO 2 in coal seams has become an attractive carbon sequestration technology for two reasons. First, the injection of CO 2 or mixtures of CO 2 and N 2 enhances methane production from coalbeds (ECBM). Second, it reduces the effect of global warming by storing CO 2 . The sequestration of CO 2 in Tiffany and Allison fields in the San Juan Basin is an example of this technology. The efficiency of this process is strongly dependent on the wetting behavior of the coal-water-CO 2 system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…carboxylic or phenolic groups [35]; the concentration of these functional groups depends on the coal rank ( [36] see also FTIR discussion in Section 3.5). The results found here are consistent with Ibrahim and Nasr-El-Din [37] who reported that both zeta potentials and contact angles on coals increased with salinity. Fuerstenau et al [38] reported that for low ash anthracite coal, the zeta potential was measured to be -25 mV at 0.01 M NaCl (pH = 7) at room temperature.…”
Section: Effect Of Salinity On Zeta Potential and Contact Anglesupporting
confidence: 93%
See 1 more Smart Citation
“…carboxylic or phenolic groups [35]; the concentration of these functional groups depends on the coal rank ( [36] see also FTIR discussion in Section 3.5). The results found here are consistent with Ibrahim and Nasr-El-Din [37] who reported that both zeta potentials and contact angles on coals increased with salinity. Fuerstenau et al [38] reported that for low ash anthracite coal, the zeta potential was measured to be -25 mV at 0.01 M NaCl (pH = 7) at room temperature.…”
Section: Effect Of Salinity On Zeta Potential and Contact Anglesupporting
confidence: 93%
“…Moreover, θa increased from 52° to 60° and θr increased from 44° to 53° when brine composition changed from 1 wt% NaCl to 1 wt% MgCl2 ( Figure 6). The results are consistent with [37] who also reported that coal/brine zeta potentials increased for divalent cations (Ca 2+ and Mg 2+ ). Harvey et al [39] also found that MgCl2 brine resulted in an increase in zeta potential.…”
Section: Effect Of Brine Composition On Zeta Potential and Contact Anglesupporting
confidence: 92%
“…Moreover, we found similar trends for low, medium and high rank coals (Figure 7). In the literature, there is a lack of data on the effect of salinity on CO2-wettability of coal, yet our results are consistent with Ibrahim et al [52], who analysed contact angles of CO2-brine-coal systems for brine salinities varying between 0 g/L-15 g/L NaCl), and who reported that contact angles were highest for 15 g/L and lowest for DI water.…”
Section: Effect Of Brine Salinity On Co2-wettability Of Coalsupporting
confidence: 92%
“…Fig. Ibrahim and Nasr-El-Din (2015b) showed that the CO 2 adsorption increased as water salinity increased. It shows that, as the injection flow rate increased, the ⌬dps slightly decreased.…”
Section: Results and Discussion: Experimentalmentioning
confidence: 95%